State fragility: towards a multi-dimensional empirical typology - Jörn Grävingholt; Sebastian Ziaja; Merle Kreibaum (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
The purpose of this paper is to demonstrate that, empirically, state fragility – conceptualised as a multi-dimensional phenomenon along the categories of authority, capacity and legitimacy – comes in several distinct configurations, yet that the number of such configurations is rather limited. We suggest that this finding has useful, previously unexplored implications for policy design vis-à-vis fragile states. We do not intend to call into question the necessity of country-specific analysis. A better grasp of “typical” forms of fragility, however, should help development agencies to better prepare for the types of situations they are most likely to be confronted with. The final section of the paper explores some of the practical implications that can be derived from our classification.
Keywords: 330; Demokratie und Autokratie; Governance; Sicherheit; Frieden und fragile Staaten